Polskie dwudziestowieczne przekłady Osmana Ivana Gundulicia / Polish 20th century translations of Osman by Ivan Gundulić - Gostomska, Anita (Przekłady Literatur Słowiańskich, 2019)
In this paper, I would like to present the story of two Polish 20th century translations of Osman by baroque poet Ivan Gundulić. In the production process of the translation there were involved three main actors: Croatian initiator of the whole process, Julije Benešić, and the two translators, Czesław Jastrzębiec-Kozłowski and Jerzy Pogonowski.